2019
DOI: 10.31533/pubvet.v13n3a293.1-9
|View full text |Cite
|
Sign up to set email alerts
|

Potencial biológico y estudio in vitro de la digestión de péptidos solubles de diferentes variedades de queso

Abstract: Resumo. Atualmente, a preocupação com a qualidade de vida tem elevado o consumo de alimentos promotores de saúde, sendo assim, pesquisas em busca de compostos naturais que exerçam atividade biológica se intensificaram na última década. Objetivou-se avaliar as atividades antioxidantes, quelante de íons Fe 2+ e Cu 2+ , anti-hipertensiva de proteínas e peptídeos hidrossolúveis dos queijos de coalho bubalino e bovino, gorgonzola, mussarela, cheddar e ricota. As atividades antioxidantes foram realizadas empregando … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…However, peptides present in food are subject to further hydrolysis when exposed to digestive processes and may lose some functional characteristics [10]. When studying the biological and in vitro digestion potential of soluble peptides obtained from various kinds of cheese, Santos et al [85] found that bovine and buffalo Coalho cheese, gorgonzola, mozzarella, cheddar, and ricotta had antioxidant activity both before and after in vitro digestion.…”
Section: Antioxidantmentioning
confidence: 99%
“…However, peptides present in food are subject to further hydrolysis when exposed to digestive processes and may lose some functional characteristics [10]. When studying the biological and in vitro digestion potential of soluble peptides obtained from various kinds of cheese, Santos et al [85] found that bovine and buffalo Coalho cheese, gorgonzola, mozzarella, cheddar, and ricotta had antioxidant activity both before and after in vitro digestion.…”
Section: Antioxidantmentioning
confidence: 99%